2019
DOI: 10.4143/crt.2018.424
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Breast Conserving Surgery Followed by Radiation Therapy with Mastectomy Alone for Pathologic N1 Breast Cancer Patients in the Era of Anthracycline Plus Taxane-Based Chemotherapy: A Multicenter Retrospective Study (KROG 1418)

Abstract: Purpose We compared the oncologic outcomes of breast-conserving surgery plus radiation therapy (BCS+RT) and modified radical mastectomy (MRM) under anthracycline plus taxane-based (AT) regimens and investigated the role of adjuvant radiation therapy (RT) in patients with pathologic N1 (pN1) breast cancer treated by mastectomy. Materials and Methods We retrospectively reviewed the medical records of 2,011 patients with pN1 breast cancer who underwent BCS+RT or MRM alone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…The value of RNI in patients with T1-2N1M0 breast cancer remains a topic of great clinical relevance and controversy. Our results showed that the 5-year LRR was 7.2% in patients with T1-2N1M0 breast cancer without RNI, which is consistent with other contemporary studies showing that the 5-year LRR was less than 10% ( 9 , 17 19 ). Given the low LRR risk, the necessity of RNI in T1-2N1M0 breast cancer has been questioned.…”
Section: Discussionsupporting
confidence: 92%
“…The value of RNI in patients with T1-2N1M0 breast cancer remains a topic of great clinical relevance and controversy. Our results showed that the 5-year LRR was 7.2% in patients with T1-2N1M0 breast cancer without RNI, which is consistent with other contemporary studies showing that the 5-year LRR was less than 10% ( 9 , 17 19 ). Given the low LRR risk, the necessity of RNI in T1-2N1M0 breast cancer has been questioned.…”
Section: Discussionsupporting
confidence: 92%
“…Although breast cancer ranks second, behind lung cancer, in the number of new cancer cases (12%), it has a relatively low death rate (7%), ranking fifth next to liver cancer. This higher survival rate might be credited to the advancement of traditional therapies such as radiotherapy 3,4 chemotherapy 5–8 , surgery 9 and to the development of relatively newer therapies such as hypothermia and hyperthermia that uses nanotechnology 1013 and immunotherapy 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Given this situation, we applied propensity score matching to balance the clinical T-stage and N-stage. Propensity score matching was used recently to compare BCS and mastectomy in several retrospective studies ( 23 , 24 ). After propensity score matching, clinical T-stage (P=0.144) and clinical N-stage (P=0.744) were no longer significantly different between the two groups ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%